War is all hell : the nature of evil and the Civil War - Blum, Edward J.; Matsui, John H., 1981- (Philadelphia : University of Pennsylvania Press, 2021)
"An examination of how Americans brought concepts of the devil, demons, and hell into every fabric of their lives and times in the American Civil War. These influences continued to impact the nation and its people after the war"--
Slavery, secession, and Satan -- An earthly hell -- Masks and faces -- To fight like devils -- Hell let loose -- The God of this world.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Good and evil -- Social aspects -- United States -- History -- 19th century; Good and evil -- Political aspects -- United States -- History -- 19th century; Devil -- Social aspects -- United States -- History -- 19th century; Devil -- Political aspects -- United States -- History -- 19th century; United States -- History -- Civil War, 1861-1865 -- Religious aspects; United States -- Religion -- 19th century; United States -- Civilization -- 19th century; United States -- History -- Civil War, 1861-1865 -- Influence; Démon -- Aspect social -- États-Unis -- Histoire -- 19e siècle.; Démon -- Aspect politique -- États-Unis -- Histoire -- 19e siècle.; États-Unis -- Religion -- 19e siècle.; États-Unis -- Civilisation -- 19e siècle.; HISTORY -- United States -- 19th Century; Civilization; Devil -- Social aspects; Good and evil -- Social aspects; Influence (Literary, artistic, etc.); Religion; War -- Religious aspects; United States; 1800-1899; American History; American Studies; History